No Reason to Focus on Emotional Episodes - Díaz, Rodrigo (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
Christine Tappolet’s book Philosophy of Emotion: A Contemporary Introduction, like many other works in emotion theory, focuses primarily on emotional episodes at the expense of so-called “emotional dispositions.” I argue that there is no reason for theories of emotion to focus on emotional episodes or to reserve the term “emotion” for them.